Effect of Thoracic Manipulation Along With Neck Stabilization Exercises On Pain and Range Of Motion In Subjects With Mechanical Neck Pain - K Kamble, Kiran; B Shinde, Sandeep (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND—Mechanical neck pain is a musculoskeletal disorder characterized by pain, stiffness, and reduced cervical and thoracic spine range of motion. People of the age group 25-35 years are most commonly associated with these symptoms. Hence, this study is conducted to improve neck muscle function and reduce symptoms.OBJECTIVES—To determine the effect of thoracic manipulation along with neck stabilization exercises on pain, range of motion, and cervical spine stability in subjects with mechanical neck pain.MATERIAL AND METHOD:68 individuals diagnosed with mechanical neck pain by a certified physiotherapist or an orthopedist were selected as subjects. Subjects were divided into 2 groups, 34 in each group. Group A received thoracic manipulation and neck stabilization exercises, while group B received a conventional group of exercises. Pre- and post-assessments were taken by visual analogue scale , bubble inclinometer, and stabilizer pressure biofeedback unit.RESULT: Both the groups showed improvement in pain. Range of motion and cervical spine stability. But the group is improved in comparison with group B (P